Tc-99m-Diphosphonate Uptake in a Giant Ancient Schwannoma of the Arm - Kekilli, Ersoy; Ertem, Kadir; Yagmur, Cengiz (Fırat University, 2006)
We present a 77-year woman with a size of 9.5x9x7cm giant ancient schwannoma located in the lower arm. Increased activity accumulation in the tumor was seen on the Tc-99m-methylene diphosphonate bone scintigraphy. After excision of the tumor, Pathologic diagnosis could be illustrated as an ancient schwannoma. Previous studies reported that Schwannoma could be demonstrated with increased Tc-99m-diphosphonates activity accumulation but we speculate that this accumulation may be related to tissue types or atypical types of schwannoma. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Kolda yerleşik 9.5x9x7cm boyutta dev antik schwannom'lu 77 yaşında bayanı sunmaktayız. Tc-99m-metilen difosfonat kemik sintigrafisinde tümörde artmış aktivite birikimi izlendi. Tümörün eksizyonu sonrasında patolojik tanı antik schwannom olarak gösterildi. Önceki çalışmalarda schwannom'un artmış Tc-99m-difosfonat aktivite birikimi ile gösterilebildiği yayınlanmıştır fakat biz birikimin schwannom'un doku tipleriyle veya atipik çeşitleri ile alakalı olabileceğini düşünmekteyiz. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Kolun Dev Antik Schwannom'unda Tc-99m Difosfonat Tutulumu